The effect of the illusioned image in representing the historical facts: Iraqi painting as an example - Qais Fadel Finjan; Nasser Samari Jaafar (Basrah Arts Journal, 2024)
The research was conducted tagged (the effect of the imagined image in the representation of historical facts - Iraqi painting as a model) to identify the most important historical facts and their artistic treatments in Iraqi painting, and therefore this study was built on four chapters: the first chapter (the general framework of the research): included the research problem that ended with the following question: How is the image of the scene that the artist wants to record if it is realistic or unrealistic The importance of the research and the need for it, as well as the purpose of the research and the limits of the research, and then the identification and definition of the terms contained in the title linguistically, terminologically and procedurally, as for the second chapter (theoretical framework and previous studies): it included two researchers, the first research: the concept of the imagined image, and the second research: The third chapter (research procedures): the research community and its sample, the research tool, and the analysis of the research sample included three paintings, and the fourth chapter included: the results, their discussion and conclusions, and the following are some of the results: That the artist expresses realistic historical facts recorded with perceptions far from realistic forms as an attempt to show the depth of meaning and importance of the incident. 2. The artist succeeded in making the recipient follow from the first moment to realize the nature of the work and the nature of the subject presented to him by the artist through the painting; which means that the artist was aware of the connotations that his paintings give about the embodiment of the incident and its documentation.